1,3-Alternate Calix[4]arene Functionalized With Pyrazole and Triazole Ligands as a Highly Selective Fluorescent Sensor for Hg2+ and Ag+ Ions - Chen, Yin-Ju; Chen, Meng-Yu; Lee, Kun-Ti; Shen, Li-Ching; Hung, Hao-Chih; Niu, Hao-Che; Chung, Wen-Sheng (Frontiers in Chemistry, 2020)
We report here the synthesis of a 1,3-alternate calix[4]arene 8, with bis-pyrazolylmethylpyrenes on the one end and bis-triazolylmethylphenyls on the other end, as a homoditropic fluorescent sensor for both Hg2+ and Ag+ ions. Calix[4]arene 3, with lower-rim bis-pyrazolylmethylpyrenes in cone conformation, was also synthesized as a control compound. UV-Vis and fluorescence spectra were used for metal ions screening and we found that both ligands 8 and 3 showed strong excimer emission of pyrenes when they are as a free ligand in CHCl3/MeOH (v/v, 3:1) solution, however, they both showed a high selectivity toward Hg2+ and Ag+ ions with strong fluorescence quenching and yet with different binding ratios. The fluorescence of ligand 8 was strongly quenched by Hg2+ but was only partially quenched by Ag+ ions; however, the fluorescence of ligand 3 was strongly quenched by Hg2+, Ag+ and Cu2+ ions. Job Plot experiments showed that ligand 8 formed a 1:2 complex with both Hg2+ and Ag+ ions; however, ligand 3 formed a 1:1 complex with Hg2+ but it formed a 2:3 complex with Ag+. The binding constant of ligand 3 with Hg2+ and Ag+ ions was determined by the Benesi-Hildebrand plot of UV-vis titration experiments to be 2.99 × 10E3 M-1 and 3.83 × 10E3 M-1, respectively. While the association constant of ligand 8 with Hg2+ and Ag+ was determined by Hill plot to be 1.46 × 10E12 M-2 and 9.24 × 10E11 M-2, respectively. Ligand 8 forms a strong complex with either two Hg2+ or two Ag+ ions using both the upper- and lower-rims of the 1,3-alternate calix[4]arene as the binding pockets, hence, it represents one of the highly selective fluorescent sensors for the homoditropic sensing of Hg2+ and Ag+ ions.